2023
DOI: 10.1007/s11274-023-03849-0
|View full text |Cite
|
Sign up to set email alerts
|

Survivability and proliferation of microorganisms in bentonite with implication to radioactive waste geological disposal: strong effect of temperature and negligible effect of pressure

Deepa Bartak,
Eva Bedrníková,
Vlastislav Kašpar
et al.

Abstract: As bentonite hosts a diverse spectrum of indigenous microorganisms with the potential to influence the long-term stability of deep geological repositories, it is essential to understand the factors influencing microbial activity under repository conditions. Here, we focus on two factors, i.e., temperature and swelling pressure, using a suspension of Cerny Vrch bentonite to boost microbial activity and evaluate microbial response. Suspensions were exposed either to different pressures (10, 12 and 15 MPa; to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In our study, both enrichment cultures in different media and natural incubations of bentonite suspensions were included to test which cultivation conditions were more suitable for demonstrating effects on microbial survivability. While natural incubations were successfully used in our previous experiments (Kašpar et al 2021;Bartak et al 2023) to assess the reaction of bentonite microorganisms to elevated pressure and temperature, the enrichment culture approach was clearly superior to natural incubations for detecting microbial survivability in the present study. This nding agrees well with previous studies, where excess of available nutrients promoted microbial recovery following harsh treatment, e.g.…”
Section: Bentonitementioning
confidence: 86%
“…In our study, both enrichment cultures in different media and natural incubations of bentonite suspensions were included to test which cultivation conditions were more suitable for demonstrating effects on microbial survivability. While natural incubations were successfully used in our previous experiments (Kašpar et al 2021;Bartak et al 2023) to assess the reaction of bentonite microorganisms to elevated pressure and temperature, the enrichment culture approach was clearly superior to natural incubations for detecting microbial survivability in the present study. This nding agrees well with previous studies, where excess of available nutrients promoted microbial recovery following harsh treatment, e.g.…”
Section: Bentonitementioning
confidence: 86%
“…The activity absence of IRB and SRB at 60 • C, or higher temperatures, is of particular interest related to the MIC of metal canisters previously mentioned, as this fact would retard the MIC on the canister surface. Additionally, Bartak et al [157] found a decline in microbial activity as temperature rose, and that thermal treatment significantly impacted the microbial community composition within the bentonite, identifying various thermophilic species (e.g., Caldinitratiruptor and Brockia) or thermotolerant spore-forming genera (e.g., Thermincola and Bacillus). Moreover, they determined a threshold temperature of 90 • C to inhibit microbial activity and growth across all the tested bentonite suspensions.…”
Section: Impact Of Temperature Evolution On Microorganismsmentioning
confidence: 99%